2020
DOI: 10.1002/qua.26247
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of core‐level electron spectra of ionic liquids

Abstract: On the example of 40 ion pairs (5 cations times 8 anions), this study demonstrates how the core-level binding energy values can be calculated and used to plot theoretical spectra at low computational cost using density functional theory methods. Three approaches for obtaining the binding energy values are based on delta Kohn-Sham (ΔKS) calculations, 1s KS orbital energies, and atomic charges. The ΔKS results show reasonable agreement with the available experimental X-ray photoelectron data. The 1s KS orbital e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Core level X-ray photoelectron spectroscopy (XPS) is a widely used characterization technique that allows insight into the chemical structure of molecules, solids, and surfaces. However, theoretical modeling of core electron binding energies is needed to overcome widespread difficulties of interpreting measured XPS spectra in complex materials, and this challenge has attracted significant attention in recent years. For absolute core electron binding energies of free molecules accurate and computationally efficient methods are now available. For example, the Δ-self-consistent-field (ΔSCF) method based on density functional theory (DFT) has been shown to yield highly accurate results when relativistic effects are properly accounted for, and a modern meta-generalized-gradient-approximation (meta-GGA) functional is used. It has also been shown that many-body perturbation theory in the form of full-frequency eigenvalue self-consistent GW calculations can yield accurate core electron binding energies in free molecules. , However, most experimental work is concerned with solids, not gases.…”
mentioning
confidence: 99%
“…Core level X-ray photoelectron spectroscopy (XPS) is a widely used characterization technique that allows insight into the chemical structure of molecules, solids, and surfaces. However, theoretical modeling of core electron binding energies is needed to overcome widespread difficulties of interpreting measured XPS spectra in complex materials, and this challenge has attracted significant attention in recent years. For absolute core electron binding energies of free molecules accurate and computationally efficient methods are now available. For example, the Δ-self-consistent-field (ΔSCF) method based on density functional theory (DFT) has been shown to yield highly accurate results when relativistic effects are properly accounted for, and a modern meta-generalized-gradient-approximation (meta-GGA) functional is used. It has also been shown that many-body perturbation theory in the form of full-frequency eigenvalue self-consistent GW calculations can yield accurate core electron binding energies in free molecules. , However, most experimental work is concerned with solids, not gases.…”
mentioning
confidence: 99%
“…The combination of experimental E B and theoretical models to study ILs has had limited use to date. It has been applied to study partial charges and models of a single ion or a pair (one anion with one cation). ,,,, Two studies reported calculations on larger model systems (ion “clusters”, up to eight ion pairs), but comparisons were only made for valence levels, not for core levels. , Comparisons of core E B to calculated atomic charges have also been made, which are based on the assumption that IS effects dominate E B shifts. ,,,, E B of core levels have been calculated for ILs, but rarely are core holes explicitly included and only on small scale systems such as lone ions or ion pairs. , …”
Section: Introductionmentioning
confidence: 99%
“…25,64,66,67,69 E B of core levels have been calculated for ILs, 65 but rarely are core holes explicitly included and only on small scale systems such as lone ions or ion pairs. 38,68 The XPS signal from an IL arises from contributions from a distribution of E B values that reflects the range of chemical environments coexisting in the IL. Thus, the broadening of an experimental XPS core level peak has the potential to give information about the geometric structure of a sample.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the prediction of 1s core electron binding energies in the elements carbon to fluorine has attracted the most attention. 2–24 In addition, a few studies have considered the 2p core levels of elements of the third row of the periodic table. 2,3,7–11…”
Section: Introductionmentioning
confidence: 99%